Role of adipocyte browning in prostate and breast tumor microenvironment - Hui-Chen Ku; Ching-Feng Cheng (Tzu Chi Medical Journal)
Prostate cancer (PC) and breast cancer (BC) are the most common cancers in men and women, respectively, in developed countries. The increased incidence of PC and BC largely reflects an increase in the prevalence of obesity and metabolic syndrome. In pathological conditions involving the development and progression of PC and BC, adipose tissue plays an important role via paracrine and endocrine signaling. The increase in the amount of local adipose tissue, specifically periprostatic adipose tissue, may be a key contributor to the PC pathobiology. Similarly, breast adipose tissue secretion affects various aspects of BC by influencing tumor progression, angiogenesis, metastasis, and microenvironment. In this context, the role of white adipose tissue (WAT) has been extensively studied. However, the influence of browning of the WAT on the development and progression of PC and BC is unclear and has received less attention. In this review, we highlight that adipose tissue plays a vital role in the regulation of the tumor microenvironment in PC or BC and highlight the probable underlying mechanisms linking adipose tissue with PC or BC. We further discuss whether the browning of WAT could be a therapeutic strategy for the treatment of PC and BC.